Temporal Characteristics Of Microwave Radiations Emitted By Narrow Bipolar Events In Tropical Thunderstorms - Seah, Boon York (2020)
A lightning flash starts with the very first process called electron avalanche followed by streamer and leader. Each process has their own peaked frequency band, such as the leader is peaked between Very Low Frequency (VLF) and Low Frequency (LF) bands while streamer is peaked at Very High Frequency (VHF) band. However, the peak frequency band of electron avalanche cannot be determined with certain. There are two postulations regarding the peak frequency of electron avalanche. First postulation suggests that electron avalanche peaked at VHF band while the second suggests electron avalanche peaked in microwave band. All simulation results suggest that electron avalanche emits strong microwave radiations. On the other hand, all experimental works were more focus on the characteristics of microwave radiation for each lightning event such as initial breakdown and return stroke rather than investigating whether microwave radiation emitted by electron avalanche or not. The significance of this project was the contribution of the new knowledge in lightning initiation by designing a microwave receiver and distinguishing the difference between microwave and VHF radiations emitted by lightning flashes. As the streamer is preceded by electron avalanche, detecting microwave radiation before the onset of VHF could be used as a method to prove that electron avalanche emits strong microwave radiation. In this thesis, microwave radiations associated with Narrow Bipolar Events (NBEs) have been chosen to analyze the onset time of both microwave and VHF radiations. In order to detect the microwave radiation, a finite-length and small air-gap parallel plates antennas with resonance frequency around 1 GHz were designed and fabricated. Then, the temporal characteristics of these microwave waveforms were analysed and compared to their corresponding VHF and LF/VLF waveforms. A total of 74 NBEs accompanied by the VHF and microwave radiations have been recorded and analysed. Microwave radiations of 16 NBEs were found to lead VHF and fast antenna (LF/VLF) records with lead time of 125.53 ± 81.32 ns and 600.65 ± 222.34 ns, respectively. Both burst trains of VHF and microwave radiations are consisting of Rising Phase (RP) and Damping Phase (DP). A total of 21 microwave and 22 VHF waveforms were found to have Initial Stage (IS) at the earlier part of the RP with clear bipolar shape waveform. Moreover, 27 VHF burst trains consist of a kind of unique temporal characteristic named as Quiet Phase (QP) where VHF radiation was absent, which was not found in any microwave radiations. This might be the transient period for the electron avalanche at a streamer tip delayed due to the attachment factor,